2021
DOI: 10.1155/2021/5588483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adjuvant Use of Midodrine to Intravenous Vasopressors: A Systematic Review and Meta-Analysis

Abstract: Purpose. To evaluate the efficacy and safety of midodrine use in intensive care units (ICU) to facilitate weaning off intravenous vasopressors (IVV). Methods. We searched PubMed/MEDLINE, Cochrane library, and Google Scholar (inception through October 18th, 2020) for studies evaluating adjuvant use of midodrine to IVV in the ICU. The outcomes of interest were ICU length of stay (LOS), hospital LOS, mortality, IVV reinstitution, ICU readmission, and bradycardia. Estimates were pooled using the random-effects mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Exploratory analysis showed no difference in results according to the dose of midodrine in included studies. Our study results are in accordance with a prior meta-analysis of observational studies by Al-Abdouh et al, who also demonstrated that the use of midodrine was not associated with significant difference in ICU LOS, hospital LOS, mortality, or ICU readmissions [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Exploratory analysis showed no difference in results according to the dose of midodrine in included studies. Our study results are in accordance with a prior meta-analysis of observational studies by Al-Abdouh et al, who also demonstrated that the use of midodrine was not associated with significant difference in ICU LOS, hospital LOS, mortality, or ICU readmissions [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study by Hammond et al 12 involved 3 observational studies, one of which was a non-peer-reviewed abstract. Our study results were comparable with the meta-analysis conducted by Al-Abdouh et al 13 in 2021, which also showed nonsignificant differences for ICU and hospital LOS when using midodrine in addition to IVVs. The meta-analysis by Al-Abdouh et al 13 was conducted using 6 studies, 5 of which were observational and only 1 of them was a randomized controlled trial (MIDAS trial) by Santer et al 5 There are several limitations to our study that should be acknowledged.…”
Section: Utility Of Midodrine During the Recovery Phase Of Shock: A S...supporting
confidence: 91%
“…This finding is in keeping with the primary outcome of MIDAS, the only appropriatelypowered, randomised study of this question, 7 as well as several other studies and meta-analyses which showed no effect of midodrine on similar outcomes. [12][13][14][15] Earlier retrospective or observational studies demonstrated that midodrine accelerated either liberation from vasopressors or discharge from the ICU. 1,6,16 These differences are likely due to heterogeneous study populations, retrospective or observational designs and differing dose regimens.…”
Section: Discussionmentioning
confidence: 99%